Active Site Dependent Reaction Mechanism over Ru/CeO2 Catalyst toward CO2 Methanation - Wang, Fei; He, Shan; Chen, Hao; Wang, Bin; Zheng, Lirong; Wei, Min; Evans, David G; Duan, Xue (Journal of the American Chemical Society, 2016)
Oxygen vacancy on the surface of metal oxides is one of the most important defects which acts as the reactive site in a variety of catalytic reactions. In this work, operando spectroscopy methodology was employed to study the CO2 methanation reaction catalyzed by Ru/CeO2 (with oxygen vacancy in CeO2) and Ru/α-Al2O3 (without oxygen vacancy), respectively, so as to give a thorough understanding on active site dependent reaction mechanism. In Ru/CeO2 catalyst, operando XANES, IR, and Raman were used to reveal the generation process of Ce3+, surface hydroxyl, and oxygen vacancy as well as their structural evolvements under practical reaction conditions. The steady-state isotope transient kinetic analysis (SSITKA)-type in situ DRIFT infrared spectroscopy undoubtedly substantiates that CO2 methanation undergoes formate route over Ru/CeO2 catalyst, and the formate dissociation to methanol catalyzed by oxygen vacancy is the rate-determining step. In contrast, CO2 methanation undergoes CO route over Ru surface in Ru/α-Al2O3 with the absence of oxygen vacancy, demonstrating active site dependent catalytic mechanism toward CO2 methanation. In addition, the catalytic activity evaluation and the oscillating reaction over Ru/CeO2 catalyst further prove that the oxygen vacancy catalyzes the rate-determining step with a much lower activation temperature compared with Ru surface in Ru/α-Al2O3 (125 vs 250 °C).